CONGENITAL DIAPHRAGMATIC HERNIA - Aziz, Farida; Mohammad, Gul; zeb, Aurang (Journal of Ayub Medical College Abbottabad, 1992)
ABSTRACT The exact incidence of herniation through diaphragm is difficult to assess. If oesophageal Hiatal Hernia is excluded, a diaphragmatic Hernia in a child is usually through Foramen of Bochdalek on left side. The Foramen of Morgagni is involved much less frequently. The commonest and most important type of Diaphragmatic Hernia is through the patent pleureperitonial canal (Bochdalek). This causes trouble on the left side more often than on the right, where the liver blocks off all but large hernias. This paper is a report of two cases with delayed onset type of Hernia which were repaired surgically after confirmation of diagnosis.